The Six-Minute Walking Exercise on The Fatigue Levels in Hemodialysis Patients - Yohanes Gamayana Trimawang Aji; Krisna Yetti; Lestari Sukmarini (PUINOVAKESMAS, 2020)
Patients undergoing routine hemodialysis are often experiencing fatigue. One of the interventions was made to minimize the level of fatigue through the six-minute walking exercise. This study aims at investigating the effectiveness of the six-minute walking exercise on the decreasing level of fatigue in patients undergoing hemodialysis. The method used is quasi-experiment with pretest-posttest control group design. Sixteen HD patients were recruited into two groups: the exercise training group (n= 8) and the control group (n= 8). The six-minutes walking was conducted in March - April 2017 in the hemodialysis room of Fatmawati Hospital Jakarta. Results indicated a significant decrease in fatigue level in the intervention group after four six-week walking exercises over a 2-week period. This is evidenced in the intervention group, there is a decrease in fatigue level from the category of moderate fatigue to mild fatigue. Six-minute walking exercise can be applied and developed by nurses as a part of a health education program to decrease fatigue levels in patients undergoing hemodialysis.